2023
DOI: 10.3390/en16155653
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Agent Reinforcement Learning Method for Cooperative Secondary Voltage Control of Microgrids

Abstract: This paper proposes a novel cooperative voltage control strategy for an isolated microgrid based on the multi-agent advantage actor-critic (MA2C) algorithm. The proposed method facilitates the collaborative operation of a distributed energy system (DES) by adopting an attention mechanism to adaptively boost information processing effectiveness through the assignment of importance scores. Additionally, the algorithm we propose, executed through a centralized training and decentralized execution framework, imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…The second feature of the MARL-based control is the more precise stability and balance that can be accomplished (in principle) in the control process due to the several cascade-correction stages, as shown in the general structure of the conventional multiagent- Multiagent primary-secondary management was a prominent recent MARL application for solving power-flow management in modern decentralized networks, especially managing power-storage flow. Thus, many recent power-management research works have suggested the active and successful applications of managing energy-storage systems based on MARL, where the management of battery-energy-storage systems was the most successful [10,26,27]. The success of the abovementioned MARL-based control is promoted by three fundamental features.…”
Section: Article Structurementioning
confidence: 99%
“…The second feature of the MARL-based control is the more precise stability and balance that can be accomplished (in principle) in the control process due to the several cascade-correction stages, as shown in the general structure of the conventional multiagent- Multiagent primary-secondary management was a prominent recent MARL application for solving power-flow management in modern decentralized networks, especially managing power-storage flow. Thus, many recent power-management research works have suggested the active and successful applications of managing energy-storage systems based on MARL, where the management of battery-energy-storage systems was the most successful [10,26,27]. The success of the abovementioned MARL-based control is promoted by three fundamental features.…”
Section: Article Structurementioning
confidence: 99%